Cost-effectiveness of blood agar for isolation of mycobacteria. - Michel Drancourt; Didier Raoult (Public Library of Science (PLoS), 2007)
BACKGROUND: Mycobacterium species are grown using specific media that increase laboratory cost, thus hampering their diffusion in resource-limited countries. Preliminary data suggested that versatile blood agar may be also used for mycobacterial culture. METHODOLOGY: We examined the growth of 41 different Mycobacterium species on 5% blood agar. Over a 24-month period we analysed isolation of mycobacteria after parallel inoculation of clinical specimens into both a reference automated system (BACTEC 9000 MB broth) and 5% blood agar slant tubes, after NaOH decontamination, and compared the cost of performing 1,000 analyses using these two techniques. CONCLUSIONS: Mycobacterium reference species cultured on blood agar, with the exception of Mycobacterium ulcerans. Inoculation of 1,634 specimens yielded 95 Mycobacterium isolates. Blood agar performed significantly more efficiently than BACTEC 9000 MB broth (94 vs 88 isolates, P = 0.03). Decontamination of Candida albicans in 5 specimens by addition of amphotericin B in blood agar yielded one more M. tuberculosis isolate that could not be isolated in BACTEC broth. Uneven distribution of time to culture positivity for M. tuberculosis had a median (range) of 19+/-5 days using blood agar and 26+/-6 days using BACTEC 9000 MB broth. Cost for 1,000 analyses in France was estimated to be of 1,913 euros using the blood agar method and 8,990 euros using the BACTEC 9000 MB method. Blood agar should be regarded as a first-line medium for culturing Mycobacterium species. It saves time, is cost-effective, is more sensitive than, and at least as rapid as the automated method. This is of particular importance for resource-limited countries in which the prevalence of tuberculosis is high.